Development of Geometry Learning Tools Integrated Transformation of Ethnomathematics of Jambi Batik - Tiya Marsya; Ahmad Fauzan; Edwin Musdi (Postgraduate, University of Mataram, 2023)
This research was motivated by low student learning outcomes, learning tools that did not provide a positive relationship to students' mathematical abilities, and learning tools that did not include the surrounding culture. This research aims to produce an integrated learning tool for Jambi Batik ethnomathematics that meets the valid, practical, and effective criteria for transforming geometry material in class IX junior high schools. The method used in this research is a combination of ethnographic research and development research with the Plomp model which consists of the Preliminary, Prototyping, and Assessment Phases. The subjects of this research were class IX students of SMP Negeri 21 Batanghari. The results of this research show that the Jambi Batik Ethnomathematics integrated Transformation Geometry learning tool in Class IX Middle School is valid. The device also meets practical criteria based on the results of questionnaires and interviews. Based on the final tests carried out, it shows that the device is in the effective category. So, it can be concluded that the resulting device is valid, practical, and effective.